Oxidative stress in newborn kids and does submitted to different antenatal corticosteroid therapy - Maschio, Eva Liliane dos Santos Silva [UNESP]; Narciso, Luis Gustavo [UNESP]; Trevizan, Juliane Teramachi [UNESP]; Bovino, Fernanda [UNESP]; Vieira, Dielson da Silva [UNESP]; Mendes, Luiz Cláudio Nogueira [UNESP]; Peiró, Juliana Regina [UNESP]; Alcindo, Jefferson Filgueira; de Almeida, Breno Fernando Martins; Feitosa, Francisco Leydson Formiga [UNESP] (Elsevier, 2023)
The objective of this study was to evaluate the influence of different corticosteroid protocols performed in pregnant does on oxidative stress markers of newborn kids born with 141 days of gestation and does. Reactive oxygen metabolites (D-ROMs) and biological antioxidant potential (BAP) were examine in response to the following four protocols: GI (does: n = 4; newborns kids: n = 7) with a single dose of 20 mg dexamethasone, 2 days prior to elective surgery (139 days of gestation); GII (does: n = 4; newborns kids: n = 6) 2 mg dexamethasone (133–136 days); 4 mg (137−139); and 20 mg at 140 days; GIII (does: n = 4; newborns kids: n = 7) with a dose of 16 mg of dexamethasone (139 days), with repeated doses at 12-h interval until elective surgery; and GIV (does: n = 4; newborns kids: n = 6) using doses of 4, 8, 16, and 20 mg dexamethasone (137, 138, 139, and 140 days). Samples were collected from does 15 min (DM15) after birth and from newborn kids 15 min (M15), 24 h (M24), and 48 h (M48) after birth. When verifying the effect of time in each group, newborn kids from GII, GIII, and GIV presented lower concentrations of D-ROMs at M15 when compared to M48. Newborn kids from GIII and GIV showed increased BAP values at M24 and M48 when compared to M15, respectively. Comparisons between treatments revealed that newborn kids from GI presented higher D-ROMs than those of GII at M15 and GIV at M48. GIV presented higher BAP values than GI, GII, and GII at M48. No significant differences among does were observed considering D-ROMs or BAP values. The protocol for the administration of corticosteroids in does influence the oxidative stress response in newborn kids.
Keywords: Antioxidant; Dexamethasone; Goats; Oxidant; Premature